2018
DOI: 10.1186/s13002-018-0212-0
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses of medicinal plants used by Indigenous communities for veterinary practices at Bajaur Agency, Pakistan

Abstract: BackgroundThe pastoral lifestyle of Indigenous communities of Bajaur Agency is bringing them close to natural remedies for treating their domestic animals. Several studies have been conducted across the globe describing the importance of traditional knowledge in veterinary care. Therefore, this study was planned with the aim to record knowledge on ethnoveterinary practices from the remote areas and share sit with other communities through published literature.MethodsData was gathered from community members thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 70 publications
(92 reference statements)
6
60
1
2
Order By: Relevance
“…This result is like the study reported in Chail valley, Tehsil Kabal District Swat Pakistan [32]. However, the antimicrobial, phytochemical and traditional studies of selected medicinal work have been published in Bajaur agency, Pakistan [25,32,34,35].…”
Section: Medicinal Plant Diversitysupporting
confidence: 77%
“…This result is like the study reported in Chail valley, Tehsil Kabal District Swat Pakistan [32]. However, the antimicrobial, phytochemical and traditional studies of selected medicinal work have been published in Bajaur agency, Pakistan [25,32,34,35].…”
Section: Medicinal Plant Diversitysupporting
confidence: 77%
“…Three species were contributed by each of Moraceae, Asclepiadaceae, Polygonaceae, Brassicaceae, Solanaceae, Cucurbitaceae, and Liliaceae. Of the remaining eight families, namely, Poaceae, Pinaceae, Zingiberaceae, Chenopodiaceae, Plantaginaceae, Apiaceae, Fabaceae, and Zygophyllaceae, each one contributed two species [ 19 , 20 ]. Asteraceae, Lamiaceae, and Rosaceae were also reported with a high number of plants used for medicinal purposes.…”
Section: Resultsmentioning
confidence: 99%
“…The level of indigenous knowledge on medicinal uses of the plant species of family Poaceae was more prevent in illiterate (around 80%) and less educated people and rest of informations were shared by the educated informants but well educated informants were less conversant on the ethnomedicinal uses of plant species, particularly of Poacease taxa. High level of exposure to modernization and dependence of allopathis medicines could be the reason behind this, which have already been reported [49,50]. Though, previous studies were focused on a single community having one ethic group and same culture [51], but in the last few decades ethnobiologists are more interested in cross cultural variation of traditional knowledge of different communities and ethnic groups [52].…”
Section: Demographic Featuresmentioning
confidence: 92%
“…It has been recorded that neighbouring indigenous communities share more common traditional practice of plants as medicines in order to cure various ailments and this is because of more social trade and sharing of ethnomedicinal knowledge among native groups [132,133]. In contrast, a low similarity index indicates less sharing of medicinal knowledge and low social interaction that could have been happened in the past bringing more difference in ethnobotanical practices [50]. Geological isolation of ethnic groups and plants resulted a significant change in vegetation structure and therapeutic uses of indigenous plants and this may be a reason for loss of ethnobotanical information [44].…”
Section: Jaccard Index (Ji)mentioning
confidence: 99%